The Effect of Good Corporate Governance, CSR, Firm Size, Leverage, and ROA on Tax Avoidance Listed on The IDX For The 2017-2021 Period - Shavira Asthalia (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2024)
This study aims to analyze the effect of corporate governance, CSR, firm size, leverage, and ROA on tax avoidance listed on the Indonesia Stock Exchange (IDX) for the period 2017-2021. The independent variables of this research are tax avoidance, CSR, GCG-BOD Independence, GCG-Institutional Ownership, and GCG-Ownership Concentration. With control variables in the form of firm size, leverage, and return on assets. The study used samples from non-financial companies that have annual reports and complete financial reports from 2017-2021, namely 1.713 data from 421 companies listed on Indonesia Stock Exchange (IDX). The collection sample in these studies used a purposive sampling method. The data studied is the company’s annual financial statements that have been audited and Corporate Social Responsibility annual reports. Data were analyzed using logistic regression analysis, where some of the variables is a dummy variable. The test results shown that GCG-BOD Independence, GCG-Institutional Ownership, firm size, and leverage have a significant effect on tax avoidance. CSR, GCG-Ownership Concentration, and ROA doesn’t have a significant effect on tax avoidance. This is shown because the larger size of the company, the more transactions will be carried out. The company’s operating income or profit will also shrink (lower) when the market tax is reduced.